Sarah as victim and perpetrator Whiteness, power, and memory in the matriarchal narrative - Reaves, Jayme R. (2018)
Womanist biblical interpretation tradition calls for white women to see themselves, not as the marginalized character, but as the text's oppressor. The text, and a community who reads that same text and has daily experiences of oppression, asks white women to recognize that, because of our position in society, we have wittingly or unwittingly been in the role of Sarah more often than we have been in the role of Hagar. Therefore, we have a responsibility to take that reality seriously by acknowledging it, delving deeper, being receptive to challenge, and allowing it to transform how we view, and operate within, the world. This article expands on and models this approach by acknowledging the ways in which the Sarah narrative has been read by white women, with a particular view to nineteenth-century historical readings in the context of American slavery as well as with an awareness of whiteness and white privilege. It seeks to dig deeper into the text to understand the fullness of Sarah's experience as both victim and perpetrator, to hear the challenge to whiteness and privilege, and to find a way to read the text that speaks to the lived experience of the oppressed as well as giving challenge to the privileged.
Keywords: #BlackLivesMatter; #MeToo; Hagar; The Handmaid's Tale; Liberation; white privilege